Pengaruh Ukuran Perusahaan Dan Kebijakan Hutang Terhadap Kebijakan Dividen Dengan Return On Assets Sebagai Variabel Moderasi - Vivendi Lordwiek; Sri Lestari Hendrayati; Golda Belladonna Umbing (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
From 2018–2022, this research will look at the IDX30 index companies listed on the Indonesian stock market to investigate how company size, debt policy, and dividend policy relate to one another, with Return On Assets acting as a moderating variable. Using secondary data culled from annual reports, this study applies quantitative research methodologies. Using a purposive selection technique, fifteen IDX30 businesses were selected as part of the research. The data is examined using moderated regression analysis in particular. This research shows that dividend policy is affected by company size and debt policy. Large corporations may see few changes to their dividend policies as a result of a limited return on assets. Also, return on assets can't mitigate how debt policy impacts dividend policy.